O PLANO TRIENAL DE INVESTIMENTOS E O IMPACTO NO TRANSPORTE FERROVIÁRIO DE CARGAS - Kloster, Alfredo Mosael (2018)
The rail cargo modality underwent transformations from the 1990s through the privatization process and the Logistics Investment Program (PIL) aimed at modernizing the country's transportation infrastructure. PIL has established guidelines aimed at re-establishing integrated transport planning. It contemplated the efficiency of the transport infrastructure with cost reduction and increase of the operational quality and the services, aiming to increase the economic competitiveness of the country. One of the requirements of the PIL was the Triennial Investment Plan (PTI) as a contractual obligation present in all the concession contracts entered into with the Railway Concessionaires (CF) in Brazil, obliging them to make a three-year investment adhering to the PTI. This study aimed to analyze the impact of investments in the production and safety of rail freight transportation, required in the field of ITP from the Concessionaires, with the purpose of evidencing whether or not the investment adhered to the purpose of the ITP. Methodologically, the impact investigation was carried out based on the investments made by 12 Railway Concessions in the period from 2014 to 2016, corresponding to the first phase of the PIL. The analyzes were carried out using descriptive statistics and the fixed and random effect panel data model, for production and safety variables in cargo transportation, whose data were collected together with the National Land Transport Agency (ANTT). The results showed that there was a positive and significant relationship between PTI investments, made and rail freight production and safety. Even presenting an inelastic return, it is concluded that the investments made by the Concessionaires in the period from 2014 to 2016 were adherent to the ITP. The study offers a method that demonstrates the investment result applied for ANTT to use in its arguments about the supervision of planned and realized projects.